SME internationalization in Sri Lanka : a dynamic capabilities perspective - Darshana Mudalige (2017)
Past research indicates that internationalization strengthens SME competitiveness and survival prospects. As SMEs are internationalizing exponentially today, theories that can expound SME internationalization have become important. Recent literature suggests that successful internationalization is associated with the owners and factors related to the firms entrenched in dynamic capabilities. Researchers argue that in a highly dynamic international business environment, dynamic capabilities lead to competitive advantage in the internationalization process. The dynamic capability framework was used to analyze the SME internationalization process in Sri Lanka. By linking the dynamic capabilities theory to individual level characteristics, this research aimed to investigate entrepreneurial orientation, social capital and human capital of the entrepreneur as important owner specific dynamic abilities leading to organizational level dynamic capabilities. Via structured questionnaires, responses from randomly selected sample of 197 internationalized SMEs in Sri Lanka was analyzed using the Partial Least Squares Structured Equation Modelling (PLS-SEM) method. This study empirically established that specific dynamic capabilities of the owner have a positive influence on the dynamic capabilities of both the organization and internationalization. The findings proved that dynamic capabilities of the organization positively influence internationalization. It established that market asset position positively influences the dynamic capabilities of the organization. The positions of the structural assets and the reputational assets of SMEs do not have a significant influence on the dynamic capabilities of the organization. It was also found that the dynamic capabilities of the organization have a mediation effect in the relationship between the specific dynamic capabilities of the owner and internationalization. The outcome of this research enhances the understanding of the SME internationalization process by highlighting the need to develop dynamic capabilities at different levels and provide insights for policy- makers and SME managers on the key capabilities required for internationalization. Keywords: dynamic capabilities, entrepreneurship orientation, SME, internationalization, social capital